2007
DOI: 10.1021/ja067067s
|View full text |Cite
|
Sign up to set email alerts
|

Radical Energies and the Regiochemistry of Addition to Heme Groups. Methylperoxy and Nitrite Radical Additions to the Heme of Horseradish Peroxidase

Abstract: The heme of hemoproteins, as exemplified by horseradish peroxidase (HRP), can undergo additions at the meso carbons and/or vinyl groups of the electrophilic or radical species generated in the catalytic oxidation of halides, pseudohalides, carboxylic acids, aryl and alkyl hydrazines, and other substrates. The determinants of the regiospecificity of these reactions, however, are unclear. We report here modification of the heme of HRP by autocatalytically generated, low-energy NO2* and CH3OO* radicals. The NO2* … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 61 publications
2
23
1
Order By: Relevance
“…The same conclusion can be drawn for an oxidative (42) or for the production of NO 2 -Tyr on a plant Hb (46). In these two cases, the nitrating agent is proposed to be the NO 2 • radical based on the peroxidase activity (pathway 3) of the hemoproteins (42,46). In fact, in these and our own studies, the possibility that H 2 O 2 might be generated inside the heme pocket cannot be entirely ruled out.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The same conclusion can be drawn for an oxidative (42) or for the production of NO 2 -Tyr on a plant Hb (46). In these two cases, the nitrating agent is proposed to be the NO 2 • radical based on the peroxidase activity (pathway 3) of the hemoproteins (42,46). In fact, in these and our own studies, the possibility that H 2 O 2 might be generated inside the heme pocket cannot be entirely ruled out.…”
Section: Discussionsupporting
confidence: 71%
“…We can exclude a direct involvement of ONOOH formed outside the protein (pathway 1) because SIN-1 did not nitrate the Lb heme and superoxide dismutase and catalase did not prevent nitration. The same conclusion can be drawn for an oxidative (42) or for the production of NO 2 -Tyr on a plant Hb (46). In these two cases, the nitrating agent is proposed to be the NO 2 • radical based on the peroxidase activity (pathway 3) of the hemoproteins (42,46).…”
Section: Discussionmentioning
confidence: 60%
“…It has been shown that these conditions lead to nitration of the porphyrin 2-vinyl group (Mb) or the 4-vinyl group (HRP). 54,55 This so-called “nitriheme” is the basis of the green coloration in cured meat upon prolonged exposure to excess nitrite under acidic conditions. Mb incubated with 50 mM nitrite leads to the formation of a 6cHS Fe(III) heme nitrito complex ( λ max 410 nm) and, upon prolonged incubation,to a 6cLS heme nitrito/nitrovinyl complex ( λ max 450 nm).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to observe that the formation of sulfonium ion bond and thioether bond was under oxidative and reducing conditions, respectively, whereas each of Met-heme and Cys-heme cross-links could be formed within the same protein scaffold of APX [44]. It should be noted that although the construction of a sulfonium ion bond in APX was succeeded, attempts to construct the bond in other peroxidases such as LPO [54] and horseradish peroxidase (HRP) [55] were unsuccessful. It suggests that the formation of a sulfonium ion bond requires stringent constraints in a protein scaffold, which might limit the application of this bond in designing artificial heme proteins.…”
Section: Sulfonium Ion Bondmentioning
confidence: 99%